METODE HIGH INTENSITY INTERVAL TRAINING SELAMA 15 MENIT DAPAT MENINGKATKAN VO2MAX DAN KECEPATAN GERAK SISWA PESERTA EKSTRAKURIKULER BULUTANGKIS SMP PGRI 2 DENPASAR - Yogie Wiswadewa; N. Adiputra; Bagus Komang Satriyasa; I Made Jawi; I P G Adiatmika; Susy Purnawati (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2017)
Background: Badminton is a game of small ball that requires a good cardiovascular endurance especially on single game. Ones training to improve cardiovascular endurance (VO2max) are high intensity interval training (HIIT), HIIT is able to overcome the problem of the lack of time if the athlete is given a cardio workout because basically the method of High Intensity Interval Training (HIIT) does not take a long time in one training session. Objective: This study aims to determine the effect of the High Intensity Interval Training methods to increase VO2max and Speed Movement. Method: This study is experimental research with the design of randomized pretest-posttest control group design, which is held in GOR Yowana Mandala Tembawu in April to May 2016. The sample was male student at SMP PGRI 2 Denpasar, who are Badminton extracurricular participants amounting to 24 students, in which divided into two groups. Both groups were given different training for 6 weeks with a frequency of exercise four times a week. Group 1 was given training jogging for 15 minutes and the group 2 was given HIIT training for 15 minutes. VO2max measured with Multistage Fitness Test (MFT) and the velocity will be measured by the 50 meter sprint tests. Result: The results showed the average test results in Group 1 before and after training VO2max values obtained respectively 34.13 ml/kg/min and 34.84 ml/kg/min and Speed Motion respectively 8.40 and 8.26 seconds seconds, while in Group 2 VO2max values obtained respectively 33.71 ml/kg/min and 40.12 ml/kg/min, while for each Motion Speed obtained 8.40 seconds and 7.41 seconds. Test results of different test with T-Independent inter group and intra-group T-Paired before and after training, Group 1 and Group 2 result p = 0.00 this indicates that p is less than 0.05 means that each training is different, significant and increasing. Conclusion: It can be concluded that High Intensity Interval Training Methods for 15 minutes improves VO2max and Speed Movement. HIIT training suggested a more intensified in the process of badminton training. Suggestions: Suggestions for further research in order to monitor physical activity, nutrition and sleep patterns of samples which will also affect the results.